2009
DOI: 10.1128/jcm.01295-09
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Mycobacterium tuberculosis from Sputum Treated with Cetyl Pyridinium Chloride

Abstract: FIG. 1.Relationship between the amount of time required for a Bactec MGIT 960 positive result and the load of AFB in sputum samples. Smear grade: 3ϩ, Ͼ10 AFB/field in at least 20 oil fields of smear; 2ϩ, 1 to 9 AFB/field in at least 50 fields; 1ϩ, 10 to 99 AFB in 100 fields; scantϩ, Ͻ10 AFB in 100 fields. For smears classified as negative, no AFB were seen in the entire smear. 4190LETTERS TO THE EDITOR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…This was further evident from the fact that no contact from the families of these index cases developed secondary tuberculosis. The TTP obtained in this study with regard to AFB load, it was comparable to our previous study [28]. Here, sputum samples from 1206 contacts were cultured for TB and overall we identified 6.9% of household contacts were culture positive for M. tuberculosis .…”
Section: Discussionsupporting
confidence: 88%
“…This was further evident from the fact that no contact from the families of these index cases developed secondary tuberculosis. The TTP obtained in this study with regard to AFB load, it was comparable to our previous study [28]. Here, sputum samples from 1206 contacts were cultured for TB and overall we identified 6.9% of household contacts were culture positive for M. tuberculosis .…”
Section: Discussionsupporting
confidence: 88%
“…After it was centrifuged at 3000 g for 15 mins, the supernatant was discarded and a portion of the deposits was used for culture. 16,17 Portion of each specimen sediment (0.5mL) was inoculated into BACTEC MGIT 960 (Becton Dickinson, Franklin Lakes, NJ07417, USA) media and incubated in an automated BACTEC MGIT 960TM machine (Becton Dickinson Diagnostic Instrument Systems) for a maximum of 42 days. Cultures exhibiting growth were subjected to light microscopy for the presence of acid-fast bacteria using Ziehl-Neelsen stain and tested by Capilia TB-Neo rapid test.…”
Section: Sputum Sample Collection Processing and Culturingmentioning
confidence: 99%
“…Once preserved specimens have reached the culture laboratory, a centrifugation step without refrigeration is necessary to remove the preservative prior to culture (12). In addition, previous studies have shown the negative effects of CPC on microscopic examination and culture systems, including (i) a significant reduction in the detection of AFB with Ziehl-Neelsen staining (14,16); (ii) an inhibition of mycobacterial growth, especially when inoculated into culture media, including Middlebrook 7H9 and 7H10 media, which have an insufficient neutralizing activity for this quaternary ammonium compound (17); and (iii) a negative effect on the Bactec MGIT 960 system, decreasing the mycobacterial detection rate and increasing the time required for mycobacterial growth readings (13). Therefore, these findings suggest a need for a simpler and cost-effective alternative to the current WHO recommendations for conducting epidemiological and drug resistance studies in resource-poor settings.…”
Section: Discussionmentioning
confidence: 99%